Efektivitas Pembelajaran Matematika Berbasis Etnomatematika Untuk Penguatan Nilai Budaya - Adelia Putri Lubis; Carlia Dermasari Sirait; Elvi Mailani; Luciana Chris May Purba; Maya Alemina Ketaren; Sofia Maharaja (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Education plays an important role in shaping students' character and competence. One of the challenges faced by the world of education is how to build students' understanding of subject matter that is relevant to the context of their daily lives. In this case, ethnomathematics is a very potential approach to be applied in mathematics learning. The purpose of this study is to examine the effectiveness of ethnomatics-based mathematics learning to strengthen cultural values. This study uses a Qualitative research method with a case study approach. This approach allows researchers to explore the experiences, perceptions, and impacts of ethnomathematics learning on students and teachers. The research subjects consisted of: students, teachers and parents. The results of this study indicate that ethnomathematics can improve students' mathematics learning achievement, especially in terms of identifying, translating, understanding the meaning of symbols, understanding and applying mathematical ideas, and making an exploration (estimate) related to mathematical concepts that is better than conventional learning.